2020
DOI: 10.1007/s11042-020-09818-1
|View full text |Cite
|
Sign up to set email alerts
|

Automated bank cheque verification using image processing and deep learning methods

Abstract: Automated bank cheque verification using image processing is an attempt to complement the present cheque truncation system, as well as to provide an alternate methodology for the processing of bank cheques with minimal human intervention. When it comes to the clearance of the bank cheques and monetary transactions, this should not only be reliable and robust but also save time which is one of the major factor for the countries having large population. In order to perform the task of cheque verification, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…AI has become state of the art for image analysis [ 25 ] and plays a role in supporting clinical decision making with respect to diagnosis and risk stratification [ 7 , 26 ]. Lakhani et al [ 27 ] recently reported a DL with CNN system to rapidly and accurately classify TB on chest radiographs with a sensitivity of 97.3% and specificity of 100.0%.…”
Section: Discussionmentioning
confidence: 99%
“…AI has become state of the art for image analysis [ 25 ] and plays a role in supporting clinical decision making with respect to diagnosis and risk stratification [ 7 , 26 ]. Lakhani et al [ 27 ] recently reported a DL with CNN system to rapidly and accurately classify TB on chest radiographs with a sensitivity of 97.3% and specificity of 100.0%.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-processing methods like noise removal and image normalization processes are utilized on the input image, earlier serving to the pixel classification process. Agrawal et al [11] used the scale-invariant feature transform method for feature extraction. Madaan et al [12] implemented convolutional neural networks for medical image classification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In summary, regression-based techniques like as YOLO and MobileNet SSD are becoming more popular for object recognition. Some of the existing research work related to object detection and identification have been discussed here -Prateek Agrawal et al [7] has suggested a technique for verifying bank checks The following information is used to verify the bank check: cheque number, bank account number, bank branch code, legal and courtesy amount, and signature. They used the IDRBT cheque dataset and deep learning-based CNN to recognise handwritten digits with a high accuracy of 99.14 percent.…”
Section: Literature Surveymentioning
confidence: 99%